Baby Food Labelling Compliance with FDA Standards in Ghana: A Cross-sectional Assessment of 104 Products - Dapaah, Vicentia; Opoku, Oscar Agyemang; Mensah, Samuel Sebe; Afful, George; Kelvin, Duah Prempeh (Lembaga Chakra Brahmanda Lentera (Chakra Brahmanda Lentera Institute) [CANDLE], 2025)
Background: Despite extensive research on consumer knowledge and attitudes toward food labelling, empirical evidence on actual manufacturer compliance with FDA labelling requirements for infant food in Ghana remains limited. Previous studies have largely focused on consumer behavior, leaving a knowledge gap regarding whether producers adhere to the 1992 Food and Drug Law and Ghana FDA standards. This study, therefore, aimed to assess the degree of compliance of infant food manufacturers in Ghana with FDA labelling requirements Methods: A cross-sectional study was conducted using purposive sampling to select 104 pre-packaged infant food products from various retail channels, including stalls, supermarkets, and malls in Kumasi, Ghana. Only commercially available pre-packaged baby foods were included; homemade or unpackaged foods were excluded. The independent variables were product origin (foreign vs. local), and the dependent variables were compliance with 15 FDA-required labelling elements. Data were collected using a structured FDA-based checklist, and data collection was supervised by the research team over a 3-week period. Reporting followed the STROBE guidelines for cross-sectional studies. Data were analyzed using Microsoft Excel 2020 for descriptive statistics (frequencies and percentages) and the chi-square test to examine associations between manufacturer origin and compliance level. Statistical significance was set at p < 0.05 Result: Overall, most products demonstrated moderate to high compliance with FDA labelling standards. Foreign manufacturers showed a higher proportion of high compliance compared to local producers. The most frequently missing labelling elements included nutrient content details and manufacturing dates. Chi-square analysis revealed a significant association between manufacturer origin and compliance level (p < 0.001), indicating that foreign companies were more likely to fully comply with FDA labelling requirements Conclusion: Infant food manufacturers in Ghana generally comply with FDA labelling standards, with foreign producers showing higher adherence than local producers. These findings highlight the need for enhanced monitoring and educational initiatives targeting local manufacturers to improve consumer safety and ensure regulatory compliance.